2019
DOI: 10.2147/cmar.s187831
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>PF4V1</em>, an miRNA-875-3p target, suppresses cell proliferation, migration, and invasion in prostate cancer and serves as a potential prognostic biomarker</p>

Abstract: BackgroundPF4V1 is a novel protein in inflammation, angiogenesis, and cancer. However, the pathogenesis, underlying mechanisms, and the prognostic value of PF4V1 in prostate cancer (PCa) are still unclear.Materials and methodsThe PF4V1 expression and relation with survival were analyzed based on a large sample size in the Cancer Genome Atlas. In vitro, the overexpression of PF4V1 was conducted in DU145 and LNCaP cells. Cell Counting Kit-8, colony formation, wound healing, and Transwell® assays were preformed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…4B). ERK1 and AKT have been reported as downstream targets of PF4V1 [19]. Therefore, we further validated the effect of hsa_circ_0069117/miR-875-3p/PF4V1 on ERK1 and AKT expression.…”
Section: Circrna Hsa_circ_0069117 Could Enhance the Expression Of Pf4...mentioning
confidence: 63%
See 1 more Smart Citation
“…4B). ERK1 and AKT have been reported as downstream targets of PF4V1 [19]. Therefore, we further validated the effect of hsa_circ_0069117/miR-875-3p/PF4V1 on ERK1 and AKT expression.…”
Section: Circrna Hsa_circ_0069117 Could Enhance the Expression Of Pf4...mentioning
confidence: 63%
“…1E). Then, we performed a literature review and found that PF4V1 has already been validated as miR-875-3p target, which was also dysregulated in several tumor diseases [19].…”
Section: Circrna Hsa_circ_0069117 Was Most Markedly Dysregulated In O...mentioning
confidence: 99%
“…PF4V1 suppresses chemokine angiogenesis by blocking the protein bFGF, and is closely associated with the growth and metastasis of various cancers [ 35 ]. It is known that PF4V1 in prostate cancer leads to suppression of proliferation and invasion, and serves as a potential prognostic biomarker [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…4C ). miR-875-3p has been reported as a tumor suppressor in prostate cancer [ 56 ], colorectal cancer [ 57 ], and hepatocellular carcinoma [ 58 ]. Down-regulation of miR-875-3p in this study suggested a similar role in breast cancer.…”
Section: Discussionmentioning
confidence: 99%